Color stability of Bulk-Fill composite restorations - Silva, Marianna-Falcão; Dias, Marlon-Ferreira [UNESP]; Lins-Filho, Paulo-Cardoso; Silva, Claudio-Heliomar-Vicente; Guimarães, Renata-Pedrosa (Medicina Oral, S.L., 2020)
Background: The color stability of the composite resin is an important property that influences its clinical longevity, which remains an inherent challenge to the material. Thus, the purpose of this study was to evaluate the color stability of bulk-fill resins when exposed to dye. Material and Methods: Cavities were prepared in 80 bovine incisors, which were randomly assigned into 4 groups (n = 20) according with the resin composite used: P60 (Control Group - Filtek P60, 3M/ESPE), FP (Filtek Bulk-Fill Posterior, 3M/ESPE), SDR (SDR, Dentsply) and FF (Filtek Bulk Fill Flow, 3M/ESPE). All restorations were performed according to the protocol of each manufacturer, the control group was restored using the incremental technique, and the other groups using single-increment technique. The color of each restoration was measured using a portable digital spectrophotometer (Easyshade-Vita) according to the CIELab system, and then the teeth were submerged in red wine for 07 days, kept in a biological oven at 37°C. New color registration was performed to measure the ΔE index of color variation. Results: The P60 group had the lowest average ΔE (16.96), while the FF group had the highest average (28.09) and ranged from 21.19 to 26.28 in the FP and SDR groups. Conclusions: Analysis of the color variation showed that the control group had better color stability than the Bulk-Fill resins evaluated.
Keywords: Dental restoration failure; Food coloring agents; polymerization